HOW AI IS SHAPING THE DIGITAL ECONOMY: A LOOK AT CHINA, THE USA, AND UZBEKISTAN - Barchinoy Ilkhomovna Khidirova (Modern American Journals, 2025)
The article examines the impact of artificial intelligence (AI) technologies on the digital economy, studying the experience of the USA, China and Uzbekistan through comparative analysis. Based on a scientific-analytical approach, artificial intelligence policies, financing mechanisms, human resource capacity and the state of technological infrastructure in these countries have been studied. According to the results of SWOT analysis, although Uzbekistan has certain opportunities for integrating artificial intelligence into digitalization of the economy, weaknesses and threats that need to be addressed in this regard have been considered. Practical recommendations have been developed for Uzbekistan in the article, including the need to train qualified specialists, strengthen international partnerships and improve the legal-regulatory framework related to AI.
Keywords: Artificial intelligence, digital economy, innovation, USA, China, Uzbekistan, comparative analysis, SWOT analysis, digital transformation, startup, technological infrastructure.